Тема пандемии в кинематографическом дискурсе (на примере фильма-притчи «Седьмая печать» И. Бергмана) - Нікоряк, Наталія; Тичініна, Альона (Tbilisi : TSU Press, 2021)
The theme of pandemic in arts (pestilence, plague, viruses) has always been quite relevant. Almost each generation that faced the similar catastrophes left rather detailed descriptions of such catastrophes. Among numerous cinema versions on the theme, particular significance is attached to a religious-philosophical parable “The Seventh Seal” by the Swedish director I. Bergman (1957). The scenario of this film is based on I. Bergman’s one-act play “Painting on Wood” (1954–1955). However, the literary constituent of the film under studies is not restricted to this play only. On the whole, it is important to point out a rich intertextual nature of the film-parable. First of all, it is biblical intertext that attracts peculiar attention – the “Book of Revelation” (Apocalypse of John, Revelation to John or Revelation from Jesus Christ) and “The Plague” by A. Camus. In addition, the author also focuses on the epos of the Middle Ages, which is adequately reflected in the personosphere, chronotope, and intermedial insertions. The issue of pandemic, viewed in the film, describes its matrix in a very special way, gradually leading the viewer to decoding the parable-allegoric element. Consequently, the film is perceived as a kind of a “culturological encyclopedia” presenting difficult times in human history, whereby mankind faced the danger of either bubonic plague, or inquisition, or mass hysteria.
The Theme of Pandemic in Cinema Discourse (on the Example of the film “The Seventh Seal “ by I. Bergman (1957)
Keywords: pandemic; movie parable; intermediate code; “The Seventh Seal”; I. Bergman